Integrated Investment Feasibility and Operational Efficiency Assessment for Small Cultural-Fashion Enterprises in the Digital Era - Nadhiroh, Alfatun; Jumali, Muhamad Abdul (LPPM Universitas Pahlawan Tuanku Tambusai, 2026)
This study evaluates the investment feasibility and business development strategy of a custom and rental kebaya enterprise in Sidoarjo. A quantitative approach was employed by calculating Net Present Value, Internal Rate of Return, and Payback Period based on actual cash flows. The results show an NPV of Rp 91.6 million, an IRR of 26.9 percent, and a payback period of 1.5 years, confirming that the enterprise is financially feasible. Operational assessment indicates a production time of 3.8 days per unit, a rework rate of 4.5 percent, a monthly output of 25 units, and a labor cost of Rp 250,000 per unit, all of which demonstrate efficient performance. These findings support the formulation of development strategies involving digital promotion, cost control, and service diversification. The study offers a practical investment-decision framework for cultural-fashion SMEs and strengthens efficiency-based creative-industry management.